BA332 Introduction to information technology : version 3 - Soh, Arthur (Singapore : International Business Unit, 1998)
Explains the concept of a computer system and the major categories of computer systems.
Introduction to information technology -- Types of computers -- Input devices -- Output devices -- Processors -- Storage devices -- Technology trends -- Application software-prductivity -- Application software-others -- System software -- Computer languages -- Methods of software acquisition -- Communication medium -- Networks -- Telecommunication -- Telecommunication equipment -- Processing techniques -- Going online -- Software interfaces -- Telecommunications concepts -- Data files & databases
Keywords: INFORMATION SYSTEM